The clinical aspects ot the sulphonylurea compounds from the position of the cardioprotective approach at patient with type 2 diabetes, using glucocardiomonitoring - N. A. Chernikova; L. L. Kamynina; A. S. Аmetov; D. A. Sychov (Сахарный диабет)
BACKGRAUND: Now the trend of Type 2 Diabetes Mellitus (T2DM) management from glucocentric to cardioprotective approach take place, and it especially relevant for the multiple group of patients with T2DM using Sulphonylurea (SU). Meanwhile the synchronized glucocardiomonitoring allowed to providing the accurate information about the cardiometabolic status of patients with T2DM.AIMS: Using the professional glucocardiomonitoring for T2DM-SU patients to investigate the relation between the glycemic variability, integral glycemic parameters and proarrhythmogenic cardiovascular events and the long-term cardiovascular outcomes.MATERIALS AND METHODS: In the observational (randomised for inclusion of patients) controlled trial the SU-patients with the T2DM duration 9,8±6,6 years were included, whom the professional glucocardiomonitoring had been made during 5 days and then the fatal and non-fatal cardiovascular events had been investigated during 5 years. RESULTS: From 283 patients with T2DM 154 patients (the basic group) used gliclazide (original drug Diabeton MB), 129 patients (the control group) used glibenclamide. The relation between the rising of the glycemic variability and cardiovascular events (the prolongation QT interval, the ST depression (dST), ventricular arrhythmias (VAs)) were demonstrated. At the basic and the control groups the coefficient of variation (CV) was 23,0±8,1 and 30,1±10,7% respectively (p<0,001), TIR-HYPO — 0,8±2,4 and 3,5±5,4% (p<0,001), the number of glycemia differences > 4 mmol/L/hr — 2,3±3,6 and 3,5±4,3 (p=0,010), the minimal glycemia level — 4,6±1,0 and 3,9±1,4 mmol/L (p=0,001). The followed differences of cardiovascular parameters were determined: QTc — 412±24 and 423±28 ms (p=0,001), dST — 0,052 [0; 0,275] and 0,109 [0; 0,422] (ratio, p=0,012), VAs — 2,2 [0; 5,9] and 3,5 [0; 8,3] (cases/pts, p=0,008). The long-term cardiovascular outcomes from the gliclazide and glibenclamide therapy (cases/100 pts-years): the total and cardiovascular death — 0,12 [0; 1,74] and 0,76 [0; 4,62] (p=0,062), cardiovascular death -0,12 [0; 1,74] and 0,62 [0; 4,08] (p=0,122), myocardial infarction — 1,56 [0; 6,94] and 2,00 [0; 8,02] (p=0,193), stroke — 0,78 [0; 4,66] and 0,76 [0; 4,62] (p=0,169), chronic heart failure — 0,52 [0; 3,72] and 1,24 [0; 6,06] (p=0,095), MACE — 2,46 [0; 10,1] и 2,62 [0; 9,38] (p=0,095), severe hypoglycemia at home — 2,46 [0; 9,12] и 7,24 [0; 16,68] (p<0,001).CONCLUSIONS: It was demonstrated that the gliclazide (original drug Diabeton MB) administration is characterized with the better quality of glycemia control, the lower glycemic variability, the lower frequency of the SU-associated hypoglycemia, dST, VAs, the lower prolongation QTc interval. The implementation of the synchronized glucocardiomonitoring is necessary for minimization of the cardiovascular T2DM-complications and for the choice of the personalized